Karakteristik Fisikokimia dan Organoleptik Biskuit dengan Pencampuran Tepung Ubi Jalar Ungu (Ipomoea Batatas) dan Tepung Ampas Kelapa - Husnul Khatimah Muchtar; Teltje Koapaha; Yoakhim Oessoe (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2022)
The purpose of this study was to determine the physicochemical and sensory characteristics of biscuits mixed with purple sweet potato flour and coconut pulp flour. The research method used was a completely randomized design (RAL) consisting of 5 treatments by mixing wheat flour, purple sweet potato flour and coconut dregs flour, namely A: (100%: 0%: 0%), B: (30%: 30%: 40), C: (30%: 40%:30%), D: (30%:50%:20%) and E: (30%: 60%:10%). The results showed that the physicochemical characteristics of biscuits were water content ranging from 2.37% - 5.75%, ash content 2.15% - 3.29%, fat content 25.03% - 31.05%, protein content 5.76% - 7.20%, carbohydrate content 54.51% - 60.33%, fiber crude 1.54%- 4.36% , calories 493.55-525.47 Kcal and hardness 579.78- 893.80 g.sec. The most preferred biscuit sensory test was treatment D by mixing 30% wheat flour: 50% purple sweet potato flour :20% coconut dregs flour with a taste value of 4.73 (slightly like), color 5.77 (like), aroma 5.67 (like) and textures 5.7 (like). Keywords: biscuit, purple sweet potato flour, coconut pulp flour.